"Our Birth Experiences are What Binds Us": Women's Motivations for Storytelling about Birth to Build Motherwisdom. Issue 4 (7th August 2020) - Johnson, Nicole L.; Scott, Susanna F.; Brann, Maria
ABSTRACT: Childbirth is widely considered to be a bonding experience among women. Women often feel compelled to share their story, and this research highlights communicative and reflexive aspects of storytelling as a means for meaning-making and relationship-building. This inductive thematic analysis explored 22 women's motivations for engaging in storytelling about birth across five focus groups and two one-on-one interviews. Findings demonstrate one primary theme, building motherwisdom, a term coined here to reflect the uniqueness of the birth storytelling context. We also identified three secondary themes for motivation to engage in birth storytelling: (1) fulfilling a sense of responsibility to share one's story to normalize a variety of birth experiences and to listen to learn about birth, (2) empowering women, and (3) seeking validation. Women receive positive therapeutic benefit from storytelling, and this may be particularly important in maintaining and improving mental health during the postpartum period. Our work informs the environments we can create to motivate mothers to share and listen to birth stories to foster this benefit.